Mindfulness-Based Interventions for Adolescent Social Anxiety: A Unique Convergence of Factors - Carlton, Corinne N.; Sullivan-Toole, Holly; Strege, Marlene V.; Ollendick, Thomas H.; Richey, John A. (Frontiers in Psychology, 2020)
Social anxiety disorder (SAD) is a debilitating and often chronic psychiatric disorder that typically onsets during early adolescence. Cognitive Behavior Therapy (CBT), the current “gold-standard” treatment for SAD, tends to focus on threat and fear-based systems hypothesized to maintain the disorder. Despite this targeted approach, SAD ranks among the least responsive anxiety disorders to CBT in adolescent samples, with a considerable proportion of individuals still reporting clinically significant symptoms following treatment, suggesting that the CBT-family of interventions may not fully target precipitating or maintaining factors of the disorder. This gap in efficacy highlights the need to consider new therapeutic modalities. Accordingly, this brief review critically evaluates the emergent literature supporting the use of mindfulness-based interventions (MBIs) for treating adolescent SAD. MBIs may be particularly relevant for addressing maintaining factors within this diagnosis, as they may target and interrupt cycles of avoidance and de-motivation. Despite limitations in the relative lack of randomized controlled trials (RCTs) on this topic, a unique convergence of factors emerge from the extant literature that support the notion that MBIs may hold particular promise for attenuating symptoms of SAD in adolescents. These factors include: (1) MBIs demonstrate the ability to directly engage symptoms of SAD; (2) MBIs also show consistent reduction of anxiety, including symptoms of social anxiety in adolescent populations; and (3) MBIs demonstrate high rates of feasibility and acceptability in anxious adolescent samples. We briefly review each topic and conclude that MBIs are an encouraging treatment approach for reducing symptoms of social anxiety in adolescents.